Processes of structure formation and neoformation of basalt fiber in an alkaline environment - Berdnyk, O. Yu.; Lastivka, O. V.; Maystrenko, A. A.; Amelina, N. O. (IOP, 2020)
Several approaches can be used to determine the effect of an alkaline environment on glass materials (basalt fibers). One of the most common approaches for the determination of the alkali resistance of a substance is to measure the relative mass loss after the interaction of the object of research with the alkaline environment. According to the practice guidelines, the approach involves determining the alkali resistance of a glass by measuring the mass loss per unit area of the glass under test after boiling it in an alkaline solution. But the disadvantage of this approach is it can’t be applied to basalt or another multicomponent fiberglass as it doesn’t introduce different speeds of fiber dissolution.
Keywords: basalt fibers